Environmental impact of high yield variety rice cultivation in Bangladesh: a study based on farm level data - Noor-E-Sabiha (Curtin University, 2016)
This thesis conducts a comprehensive evaluation of the environmental impact of high yield variety (HYV) rice agriculture. More specifically, this thesis estimates environmental impact-induced loss in production efficiency and evaluates environmental impact-specific external costs. Findings of this study recommends that policy makers should consider the harmfulness of specific environmental impacts and socio-environmental and agro-economic factors that determine the level of eco-efficiency and the external cost through environmental impact management projects.